Reuse of carbon fiber composite materials in porous hot mix asphalt to enhance strength and durability. (December 2019) - Zhang, Kun; Lim, Justin; Nassiri, Somayeh; Englund, Karl; Li, Hui
Highlights: Cured carbon fiber composite materials (CCFCMs) from industrial byproduct were mechanically processed for application in porous hot mix asphalt (PHMA). The inclusion of Fine CCFCMs in PHMA improved the mechanical properties and draindown resistance. As a reinforcement agent, the Fine CCFCMs improved the rutting resistance of PHMA. Abstract: Porous hot mix asphalt (PHMA) allows runoff to infiltrate through the pavement. Cured carbon fiber composite materials (CCFCM)s from aerospace production lines were ground into three size groups (Fine, Medium, and Large) and reused as reinforcement agents for PHMA in comparison to commercial synthetic fiber. The Fine CCFCMs premixed with liquid asphalt binder performed the best to reinforce PHMA in terms of indirect tensile strength and cracking resistance at both 25 °C and −10 °C. The addition of fine CCFCMs and synthetic fibers reduced the porosity by 17% and infiltration rate by up to 20%, while both fibers showed to prevent draindown of asphalt binder at an elevated temperature. The PHMA reinforced with the Fine CCFCMs performed the best in rutting resistance.